2021
DOI: 10.3390/pharmacy9040203
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Off-Label Drug Prescribing in Psychiatric Practice: A Qualitative Study

Abstract: Off-label drug prescribing (OLDP) must be based on strong scientific evidence to make sure that patients get the optimum therapeutic outcomes. Adherence to the prerequisites is determined by the physicians’ attitude and knowledge. In this context, the present study was conducted with the goal of investigating psychiatrists’ perceptions of the use of OLDP in their clinical practice. A total of 14 psychiatrists were interviewed using a semi-structured interview guide. Thematic content analysis was performed. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It was worrying that around 40% of the respondents informed their patients when prescribing an OLMU whereas more than 75% did not request informed, written / verbal consent from patient or attendant before OLMU. Shakeel et al reported that the majority of the responders did not notify the patient while prescribing an off-label ( 27 ). Varying approaches for informed consent have been proposed in Australia based on different degrees of evidence in off-label medication ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was worrying that around 40% of the respondents informed their patients when prescribing an OLMU whereas more than 75% did not request informed, written / verbal consent from patient or attendant before OLMU. Shakeel et al reported that the majority of the responders did not notify the patient while prescribing an off-label ( 27 ). Varying approaches for informed consent have been proposed in Australia based on different degrees of evidence in off-label medication ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many medications are used more often off-label than for their original indications, approved especially in pediatrics, 27,28 oncology, 29 and psychiatry. 30,31 Avastin is a medication to treat cancer, but it is also used off-label—successfully—for macular degeneration. 32,33…”
Section: Introductionmentioning
confidence: 99%
“…Many medications are used more often off-label than for their original indications, approved especially in pediatrics, 27,28 oncology, 29 and psychiatry. 30,31 Avastin is a medication to treat cancer, but it is also used off-label -successfully-for macular degeneration. 32,33 Regulating the freedom of therapy requires a type of approach in which anything that is not explicitly prohibited and is for the benefit of the patient is permitted.…”
Section: Introductionmentioning
confidence: 99%